Rosa Luxemburg Her Life and Legacy - Schulman, Jason; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2013)
Collection with new contributions to the debate from New Politics concerning the legacy of Rosa Luxemburg. Publishing Stephen Eric Bronner's essay'Red Dreams and the New Millennium' along with the numerous responses to the piece, a new introduction, and an interview with Bronner stimulates the discussion around Luxemburg's legacy.
Keywords: Science; Science; Science, general